Transformation of Social Structure in Mandeh Regency: A Sociological Study - Anggraini, Silvia; Erianjoni, Erianjoni (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the changes in the social structure of the community in Nagari Mandeh, Mandeh Subdistrict, Pesisir Selatan Regency, West Sumatra Province. Over the past decade, this nagari has undergone significant social transformation, particularly in terms of livelihood and social stratification. The main shift has occurred from traditional economic sectors such as agriculture, plantations, forestry, and fisheries toward tourism and service sectors, driven by the development of natural potential and infrastructure improvements. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation studies involving six purposively selected informants. The findings show that the people of Nagari Mandeh have been able to adapt to these changes through increased income, social mobility, and quality of life.The application of Talcott Parsons’ AGIL theory indicates that the four functions of the social system—Adaptation, Goal Attainment, Integration, and Latency—have been effectively implemented. As a result, the transformation of the social structure in Nagari Mandeh has proceeded in a balanced manner without eroding local cultural identity. These findings demonstrate that social transformation, when managed inclusively and adaptively, can lead to prosperity and sustainability for traditional communities.